Apotheker Assistenten School: Pendidikan Pertama Tenaga Farmasi di Jawa (1923-1934) - Lestari, Fathia (UIN Sunan Gunung Djati Bandung, 2025)
Health services in the Dutch East Indies have many changes. One of them is the change in efforts to eradicate diseases and epidemics. At the end of the 19th century, the Government began to take preventive efforts by organizing medical personnel education for bumiputera.This paper discusses the education of pharmaceutical workers in the Dutch East Indies. Pharmaceutical workers are one of the health workers in addition to doctors, midwives and nurses. This paper uses the historical method with four stages, namely source search, source criticism, interpretation and historical writing. The Data was found from various sources such as state archives, Dutch East Indies pharmaceutical magazine, Pharmaceutisch Tijdschrift voor Nederlands Indie, and other supporting literature. Based on the data found, it can be concluded that several things, first, the first pharmacist assistant education for bumiputera was Apotheker Assistenten School which was established in 1923-1934; second, the education produced new pharmaceutical workers from bumiputera with not many numbers. Third, the implementation of education provided by the Dutch East Indies government in the framework of government needs.